ERα is required for suppressing OCT4‐induced proliferation of breast cancer cells via DNMT1/ISL1/ERK axis. (22nd April 2019) - Jin, Xiangshu; Li, Yanru; Guo, Yantong; Jia, Yiyang; Qu, Huinan; Lu, Yan; Song, Peiye; Zhang, Xiaoli; Shao, Yijia; Qi, Da; Xu, Wenhong; Quan, Chengshi
Abstract: Objective: POU5F1 (OCT4) is implicated in cancer stem cell self‐renewal. Currently, some studies have shown that OCT4 has a dual function in suppressing or promoting cancer progression. However, the precise molecular mechanism of OCT4 in breast cancer progression remains unclear. Materials and Methods: RT‐PCR and Western blot were utilized to investigate OCT4 expression in breast cancer tissues and cells. Cell proliferation assays and mouse models were applied to determine the effects of OCT4 on breast cancer cell proliferation. DNMT1 inhibitors, ChIP, CoIP, IHC and ERα inhibitors were used to explore the molecular mechanism of OCT4 in breast cancer. Results: OCT4 was down‐regulated in breast cancer tissues, and the overexpression of OCT4 promoted MDA‐MB‐231 cell proliferation and inhibited the proliferation of MCF‐7 cells in vitro and in vivo, respectively. Two DNMT1 inhibitors (5‐aza‐dC and zebularine) suppressed OCT4‐induced MDA‐MB‐231 cell proliferation through Ras/Raf1/ERK inactivation by targeting ISL1, which is the downstream of DNMT1. In contrast, OCT4 interacted with ERα, decreased DNMT1 expression and inactivated the Ras/Raf1/ERK signalling pathway in MCF‐7 cells. Moreover, ERα inhibitor (AZD9496) reversed the suppression of OCT4‐induced proliferation in MCF‐7 cells via the activation of ERK signalling pathway. Conclusions: OCT4 is dependent on ERα to suppress the proliferation of breast cancer cells through DNMT1/ISL1/ERK axis.